Nexus Between COVID-19 Infections, Exchange Rates, Stock Market Return, and Temperature in G7 Countries: Novel Insights From Partial and Multiple Wavelet Coherence - Singh, Sanjeet; Bansal, Pooja; Bhardwaj, Nav; Agrawal, Anirudh (Frontiers in Environmental Science, 2021)
This study attempts to analyse the time-varying pattern between the exchange rates, stock market return, temperature and number of confirmed COVID-19 cases in G7 countries by the COVID-19 pandemic. We have implemented our analysis using the Wavelet Coherence (WC) and Partial Wavelet Coherence (PWC) on independent variables from 4th January 2021 to 31st July 2021. This paper contributes to the earlier work on the same subject by employing Wavelet Coherence to analyse the effect of the sudden upsurge of the COVID-19 pandemic on exchange rates, stock market returns and temperature to sustain and improve previous results regarding correlation analysis between the above-mentioned variables, We arrived at the following results (i) temperature levels and confirmed COVID-19 cases are cyclically correlated: Indicating daily temperatures have a material bearing on the propagating the novel coronavirus in G7 nations; (ii) noteworthy correlation at truncated frequencies show a material long-term impact has been observed on exchange rates and stock markets returns of G7 and confirmed COVID-19; (iii) accounting temperature and equity market returns, a more robust co-movement is observed between the exchange rate returns of the respective nations and the surge in COVID-19 cases; (iv) accounting for the influence of temperature and exchange rate returns, the increase in the confirmed number of corona virus-infected cases and equity returns’ co-movements are more pronounced. Besides academic contributions, this paper offers an insight to policymakers and investment managers alike in their attempt to navigate the impediments thrown by the coronavirus in their already ardors task of shaping the economy and predicting the stock market patterns.